Optimizing Antigen Cocktails for Detection of Mycobacterium bovis in Herds with Different Prevalences of Bovine Tuberculosis: ESAT6-CFP10 Mixture Shows Optimal Sensitivity and Specificity - Aagaard, C. (2006)
Bovine tuberculosis is a major problem in many countries; hence, new and better diagnostic tools are urgently needed. In this work, we have tested ESAT6, CFP10, PE13, PE5, MPB70, TB10.4, and TB27.4 for their potentials as diagnostic markers in field animals from Northern Ireland, Mexico, and Argentina, regions with low, medium, and high prevalences of bovine tuberculosis, respectively. At all three sites, ESAT6 and CFP10 were superior diagnostic antigens, while their combination performed even better at the two sites where the combination was tested, providing the best coverage for the detection of diseased populations. The high sensitivity in the skin test reactor groups, combined with the high specificity in the tuberculosis-free groups, indicated that a diagnosis could correctly be made for 85% of the infected animals, based on their responses to these two antigens. Furthermore, TB10.4, PE13, and PE5 have the potential to supplement ESAT6 and CFP10 in a future five-component diagnostic cocktail.